PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR PKN SISWA SD - Sari, Lili Puspita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research was to determine the effect of cooperative learning model Numbered Heads Together on learning outcomes PKn fifth grade students of SDN17 Pontianak City. Research methods that used is experimental method with Quasi Experimental Design, with Nonequivalent Control Group Design. The sample of this research are class VA consist of 34 students (control) and class VB consist of 35 students (eksperimen). Data collection techniques used What is Measurement. The collecting data tool used in the form of a multiple choice test of 35 questions. The average learning outcomes of final test class VA is 84,1 and class VB is 76,6. Based on the T test with significance, tarithmetic >ttable or 3,1>2,002 α=5% then Ha acceptable. So, the conclution is there are two average significant differences learning outcomes of students, among students group that teach with apply of cooperative learning model numbered head together and students group that teach with apply of cooperative learning model numbered head together. The value of effect size is 0,65 with are criteria medium, it means the use of cooperative learning model numbered heads together provide medium influence on learning outcomes PKn fifth grade students of SDN17 Pontianak City. Keywords : Numbered Head Together, Learning Outcomes